Inflationary Policy and Welfare with Limited Credit Markets - Ireland, Peter N. (Journal of Financial Intermediation, 1994)
This paper considers the costs and benefits of inflation using a stochastic version of Townsend′s turnpike model in which agents of each type are allowed to remain at a trading post for multiple periods. Numerical results show that moderate rates of inflation can be welfare-improving, but only when private credit markets are extremely limited. More generally, the existence of private credit markets curtails the ability of inflationary policy to do both harm and good. In addition, the welfare consequences of inflation depend on how much information about the economy the government has access to when implementing its policies. Journal of Economic Literature Classification Numbers: D52, E31.